Motivasi Mahasiswa Bergabung di Organisasi Intra Kampus (Studi Eksplorasi Mahasiswa Fakultas Ekonomika dan Bisnis Undip) - Firdausz, Rizky (Diponegoro Journal of Management, 2013)
This research was conducted in  the  Faculty of  Economics and Business, DiponegoroUniversity. The objective is to find out and analyze the students motivations to join the intra- campus organization. Moreover, this study also aims to discover and analyze the perception of students related to student organization as a means of softskill development.Participants of research were choosed by using   purposive sampling method and five students  were  active  in  student  organization  and  five  students  were  not  active  in  studentorganization. This study used qualitative methods in data collection and analysis.The  result  of  this  study  stated that  according to  the  five  intrinsic motivation factors consisting of goal, talent, intelligence, perspective, and interest, that perspective factor become the fundamental factor to influence student in order to join the intra-campus organization. Whereas, extrinsic motivation factors are consist of family, school, and society, school is the fundamental factors which influence student in order to join the intra-campus organization